Dry grasslands of the central valleys of the Alps from a European perspective: the example of Ausserberg (Valais, Switzerland) - Dengler, Jürgen; Widmer, Stefan; Staubli, Eline; Babbi, Manuel; Gehler, Jamyra; Hepenstrick, Daniel; Bergamini, Ariel; Billeter, Regula; Boch, Steffen; Rohrer, Sven; Dembicz, Iwona (Hacquetia, 2025)
The upper Rhone valley in the Swiss canton of Valais is one of the driest and most continental of the inner-alpine valleys and harbours a rich xerothermic flora. We studied syntaxonomy and ecology of dry grasslands and their species richness patterns. In 2018 we recorded 28 vegetation plots (10 m2) and three nested-plot series of 0.0001 to 100 m2 on the south-facing slopes above the village of Ausserberg. Mean richness of all species ranged from 1.7 on 1 cm2 to 47.3 on 100 m2, with little contribution of bryophytes and lichens. The species-area relationship for total richness closely followed a power function. Modified TWINSPAN yielded a three-cluster solution, which could easily be matched with three orders of the class Festuco-Brometea: Stipo pulcherrimae-Festucetalia pallentis (xeric, rocky), Festucetalia valesiacae (xeric, non-rocky) and Brachypodietalia pinnati (meso-xeric). The subdivision of the xeric types into two orders is new for Swiss dry grasslands, where these types up to now had been joined in a single alliance Stipo-Poion within the Festucetalia valesiacae.